Faktor-Faktor yang Mempengaruhi Orang Tua terhadap Minat Memilih Sekolah Dasar Swasta: Systematic Literature Review - Maya Diaz Restarie; Nurhattati Nurhattati; Kamaludin Kamaludin (Journal on Education, 2025)
Choosing the right school early on is very important because it will form the foundation of a child's education and experience that can affect their learning process throughout life. Parents tend to consider various factors before deciding on the right school for their child. This study aims to determine and analyze the factors that influence parents' interest in choosing a private elementary school. The method used in this study is a literature review. The analysis of the discussion shows that parents' interest in choosing a private elementary school is based on various factors, both subjective (such as recommendations and image) and objective (such as facilities and costs). These factors contribute together and influence each other in shaping parents' interest in choosing a particular school. Therefore, private schools need to consider these factors to increase the attractiveness and interest of parents in their institutions.